Safety analysis of safety‐critical systems for their applicability on NPP systems: A state‐of‐the‐art review. (7th January 2021) - Kumar, Vinay; Maurya, Ashish Kumar; Singh, Karam Veer; Singh, Lalit Kumar; Singh, Pooja; Hati, Aditya Narayan; Singh, Vibhav Prakash
Abstract: Since any risk in the safety‐critical systems (SCSs) might lead to a terrible disaster, the utmost quality attribute of these systems is safety. Researchers are putting their efforts to ensure the safety of such systems. This paper summarizes the state‐of‐the‐art in the area of the safety attribute of such critical systems. The in depth literature survey is performed to explore the several methods/models used for safety analysis of the SCS. The limitations of such methods are also shown regarding their applicability in SCS of the nuclear power plant (NPP). We also propose a framework to perform safety analysis, which can deal with these limitations and demonstrated the approach on a case study of NPP. Further, the direction for future work is advised to extend the further scope of research based on the case study.